Sul modello delle Economie della Grandezza (EG): un’entratura - Gherardi, Laura (SocietàMutamentoPolitica, 2021)
This article introduces the EG model, whose basic formulation is found in Boltanski and Thévenot’s De la justification: les économies del la grandeur (1991) - English translation: On Justification: Economies of Worth (2006). It exposes the theoretical background of the model - notably the opposition between the pragmatic sociology of critique and bourdieusian critical sociology - and its architecture both the basic one and as this has been reshaped in time. The many revisions, applications, criticisms and extensions made up to now to one of the most influential models of contemporary sociology are discussed; it is a plural and diachronic model that systematizes the sense of justice of ordinary people starting from the critiques and justifications they put forward in the course of daily disputes.